HBK-17, a 5-HT1A Receptor Ligand With Anxiolytic-Like Activity, Preferentially Activates ß-Arrestin Signaling - Pytka, Karolina; Głuch-Lutwin, Monika; Żmudzka, Elżbieta; Sałaciak, Kinga; Siwek, Agata; Niemczyk, Katarzyna; Walczak, Maria; Smolik, Magdalena; Olczyk, Adrian; Gałuszka, Adam; Śmieja, Jarosław; Filipek, Barbara; et al. (Frontiers in Pharmacology, 2018)
Numerous studies have proven that both stimulation and blockade of 5-HT1A and the blockade of 5-HT7 receptors might cause the anxiolytic-like effects. Biased agonists selectively activate specific signaling. Therefore, they might offer novel treatment strategies. In this study, we investigated the anxiolytic-like activity, as well as the possible mechanism of action of 1-[(2,5-dimethylphenoxy)propyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-17). In our previous experiments, HBK-17 showed high affinity for 5-HT1A and 5-HT7 receptors and antidepressant-like properties. We performed the four plate test and the elevated plus maze test to determine anxiolytic-like activity. Towards a better understanding of the pharmacological properties of HBK-17 we used various functional assays to determine its intrinsic activity at 5-HT1A, 5-HT2A, 5-HT7, and D2 receptors and UHPLC-MS/MS method to evaluate its pharmacokinetic profile. We observed the anxiolytic-like activity of HBK-17 in both behavioral tests and the effect was reversed by the pretreatment with WAY-100635, which proves that 5-HT1A receptor activation was essential for the anxiolytic-like effect. Moreover, the compound moderately antagonized D2, weakly 5-HT7 and very weakly 5-HT2A receptors. We demonstrated that HBK-17 preferentially activated ß-arrestin signaling after binding to the 5-HT1A receptor. HBK-17 was rapidly absorbed after intraperitoneal administration and had a half-life of about 150 min. HBK-17 slightly penetrated the peripheral compartment and showed bioavailability of approximately 45%. The unique pharmacological profile of HBK-17 encourages further experiments to understand its mechanism of action fully.